Care and the Crisis of the Paradigms of Modernity. Feminist Approaches to Subjectivity and Social Justice - Felli, Norma (B@belonline, 2024)
Covid-19 has challenged the self-concepts of neoliberal late capitalist societies, particularly the idea of the autonomous and self-sufficient individual who is “free, equal, and independent”, as well as the notions of development and growth. Social and political crises compel us to rethink the forms of associated living and the structures of modern democracies. This paper proposes feminist approaches to subjectivity and social justice, showing how these allow the development of the notion of a relational self and address today’s social challenges by proposing a justice that benefits all. The focus will be on the ethics of care, an important ethical and political paradigm. As recent publications attest, the concept-practice of care offers alternative strategies for reversing the direction of late modernity.